2022
DOI: 10.3389/fneur.2022.811298
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency Combined With Methylene Blue Paravertebral Nerve Block Effectively Treats Thoracic Postherpetic Neuralgia

Abstract: ObjectiveTo compare the effect, safety, and patient satisfaction of pulsed radiofrequency combined with methylene blue paravertebral nerve block and pulsed radiofrequency alone in the treatment of thoracic postherpetic neuralgia (PHN).MethodsA total of seventy-two patients with PHN diagnosed in the Department of Pain Management of Shengjing Hospital at China Medical University, from September 2019 to April 2021, were enrolled in the study. Patients were randomly divided into two groups. Group A (n = 36) receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Therefore, we compared the clinical efficacies and outcomes of these three therapeutic methods for ZRN patients. Our results showed that the pain intensity of ZRN patients significantly decreased under the three treatments, which was consistent with previous reports (29,30); the pain degree of group B and C patients changed from severe to moderate at 1 month and 1 week after treatment, respectively. Besides, the VAS scores were lower in group B and C compared with group A, which indicated that the combination treatments had higher efficacy in attenuating ZRN.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we compared the clinical efficacies and outcomes of these three therapeutic methods for ZRN patients. Our results showed that the pain intensity of ZRN patients significantly decreased under the three treatments, which was consistent with previous reports (29,30); the pain degree of group B and C patients changed from severe to moderate at 1 month and 1 week after treatment, respectively. Besides, the VAS scores were lower in group B and C compared with group A, which indicated that the combination treatments had higher efficacy in attenuating ZRN.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study indicated that the e cacy of combined DRG and SCS stimulation in treating chronic focal neuropathic pain was 78.9% [32] . Ji et al also reported that, after 6 months of PRF combined with nerve block for ZAP, only 16.67% of patients had an unsatisfactory prognosis [33] . These ndings consistently suggest that integrated management may be a better approach for treating refractory neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatment options for PHN include painkillers, 38 nerve blocks, 39 and electrical stimulation. 40 However, there is relatively limited research on nerve blocks and electrical stimulation at present.…”
Section: Discussionmentioning
confidence: 99%